Stingy King Meets Savvy Sage: Rethinking the Dialog between King Xuan of Qi and Mengzi. - Curzer, Howard (Dao: A Journal of Comparative Philosophy, 2020)
While the traditional interpretation takes Mengzi 孟子 to be trying to persuade King Xuan 宣 of Qi 齊, I take him to be manipulating King Xuan with insincere flattery. My interpretation has several advantages. On the traditional interpretation, Mengzi is naïve about King Xuan's motives, and confused about basic aspects of his own views, but my interpretation makes Mengzi into a canny sage with a clear, comprehensive grasp of his doctrines. My interpretation also brings the dialog into harmony with the rest of the book, and with common sense on several points. It thus makes the dialog a more nuanced, coherent, and plausible work. Next, my interpretation shows Mengzi to possess a more complete list of virtues, and a longer list of character improvement strategies than is usually thought. Finally, by attributing to Mengzi a promising strategy for curing rulers prone to rages, lust, and greed, I show that Mengzi's work fills a pressing contemporary need.